LABOUR PROTECTION SYSTEM AT PDAM TIRTA DAROY ACCORDING TO IJÂRAH 'ALA AL-'AMÂL CONTRACT - Muhammad Agiel Fahwan Gayo; Ridwan Nurdin; Badri Hasan (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
The implementation of employment contracts in a company must prioritise the welfare of workers contracted by the company even though the employment contract mechanism itself has been determined in the Law, but there are several aspects in accordance with the contract in Islamic teachings that must be applied where this is regulated in the Ijarah Ala Al Amal contract, in this study the authors took research concentration in PDAM Tirta Daroy, where how the mechanism for implementing employment contracts at PDAM TIrta Daroy has been running according to the provisions of the Ijarah Ala Al Amal contract and the Labour Law, the problems in this study are; (1) How is the legal protection system for contract workers at PDAM Tirta Daroy? (2) How is the implementation of the work contract between the management of PDAM Tirta Daroy and contract workers in improving performance and quality? (3) How is the review of the Ijarah Ala Al Amal contract on the employment protection system at PDAM Tirta Daroy. This research uses qualitative methods and descriptive analysis approaches, with data collection techniques namely interviews, documentation and questionnaires. The data analysis carried out is by looking back at the results of interviews that have been collected, then processing the data through the editing process. The author concludes that the protection of contract needs in PDAM Tirta Daroy is in accordance with the provisions set in accordance with the Ijara Ala Al Amal contract, but some aspects in the form of welfare and wages must be given more attention, especially in terms of contract labour travel costs to field work, and also the need for more supervision of the work of contract workers working in the field to avoid the risk of unwanted events in the field.